Agency From a Radical Embodied Standpoint: An Ecological-Enactive Proposal - Segundo-Ortin, Miguel (Frontiers in Psychology, 2020)
Explaining agency is a significant challenge for those who are interested in the sciences of the mind, and non-representationalists are no exception to this. Even though both ecological psychologists and enactivists agree that agency is to be explained by focusing on the relation between the organism and the environment, they have approached it by focusing on different aspects of the organism-environment relation. In this paper, I offer a suggestion for a radical embodied account of agency that combines ecological psychology with recent trends in enactive cognitive science. According to this proposal, while enactivism focuses primarily on describing how our acquired sensorimotor schemes and habits mutually equilibrate, affecting our tendency to act upon some affordances instead of others, ecological psychology focuses on studying how perceptual information contributes to the actualization of the sensorimotor schemes and habits without mediating representations, inferences, and computations. The paper concludes by briefly exploring how this ecological-enactive theory of agency can account for how socio-cultural norms shape human agency.